PENGOLAHAN LIMBAH KULIT DURIAN DI WILAYAH GUNUNGPATI MENJADI BIOPESTISIDA YANG RAMAH LINGKUNGAN - Kusumaningtyas, Ratna Dewi; Suyitno, Hardi; Wulansarie, Ria (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
Gunungpati Sub-district, Semarang is a special durian fruit producing region. One of the negative impacts of the existence of durian center in Gunungpati area is the volume of garbage leather durian accumulate. To overcome that problem, there needs to be innovation in durian skin waste management by involving the public so that durian leather waste can be utilized to be a product of economic value. One of the potential durian skin is the high essential oil content. Durian leather essential oil contains flavonoid compounds, saponins, and polyphenols that are toxic to pests and mosquitoes that can be utilized to be environmentally friendly vegetable pesticides. Therefore, to overcome the problem of high durian leather garbage volume, it is necessary to conduct commu- nity service activities aimed at providing knowledge to the community about how to increase added value for durian leather waste and provide skills to the community about how to process durian leather waste into biopesticides. In order to achieve the goals and objectives, this community service is carried out through several stages. The first phase is coordination with community leaders and lo- cal government, the second stage is the socialization to partners about the negative impact of durian leather waste and giving material about the potential of durian leather. The second stage is training to provide skills to the partner community on how to process durian leather waste into biopesticides. The third stage is the training activity of the application of biopesticide waste durian skin on the plant. The fourth phase of the activity is monitoring and evaluation. The final stage of this devotional activity is the making of reports and dissemination of devotion through scientific publication. In addition to positive impact on environmental hygiene, community service activities are also useful for empowering the economy of society to be independent and have the spirit of entrepreneurship through the innovative skills of making eco-friendly biopesticides from waste durian.